Factors that influence customer purchase intention in using online food ordering platform - Nuraisyah, Mala; Chaldun, Evy Rachmawati (Journal of Innovation, Business and Entrepreneurship, 2019)
The internet has influenced the lifestyle of people in Indonesia, including the Indonesia culinary industry. The culinary industry is the largest creative industry in Indonesia. Based on data from Badan Pusat Statistik (BPS), culinary contributed 33% to the total GDP for the Creative Industry. The purpose of this research is to investigate the factors influencing the customer in using an online food ordering platform. In some papers that are used as a reference, some variables are moderating factors on attitude and then purchase intention. However, in this research, the researcher wants to see the variables directly without using moderating factors attitude or other variables.A quantitative study was conducted among 203 respondents. Data were analyzed using multiple linear regression using SPSS for windows. Empirical results show that there are significant correlation between independent variables (trust and perceived ease of use) towards the dependent variable (purchase intention through online food ordering platform). Meanwhile another dependent variable (novelty, freshness and perceived risk, Perceived of usefulness) was not significant correlation to independent variable.Keywords: CUSTOMER PURCHASE INTENTION, ONLINE FOOD ORDERING PLATFORMS, TRUST, PERCEIVED EASE OF USE, O2O